2022
DOI: 10.1016/j.amsu.2022.103252
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for the recurrent upper gastrointestinal hemorrhage among acute peptic ulcer disease patients in Syria: A prospective cohort study

Abstract: Background Upper gastrointestinal bleeding (UGIB) is a life-threatening medical emergency characterized by bleeding from the esophagus, stomach, or duodenum. This study aims to analyze the risk factors for upper gastrointestinal tract rebleeding among acute peptic ulcer patients. Methods This is a cohort clinical study conducted between July 2018 and June 2020. Patients admitted or hospitalized because of UGIB or developed it during their hospital stay were included.s T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…The number of deaths was 13 (6.5%); which is similar to other studies [1] [4]. Our study showed a statistically signi cant relation between mortality rate and elderly (age greater than 55 years), which is similar to a study done in the United Kingdom where it showed that the most important independent prognostic predictors of mortality at three years were older age; moreover, a similar result was found in a Syrian study [8] [9]. Similar to a Syrian study, our study did not show a statistically signi cant result that the male gender is a prognostic factor, which is explained by the small size of the sample.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The number of deaths was 13 (6.5%); which is similar to other studies [1] [4]. Our study showed a statistically signi cant relation between mortality rate and elderly (age greater than 55 years), which is similar to a study done in the United Kingdom where it showed that the most important independent prognostic predictors of mortality at three years were older age; moreover, a similar result was found in a Syrian study [8] [9]. Similar to a Syrian study, our study did not show a statistically signi cant result that the male gender is a prognostic factor, which is explained by the small size of the sample.…”
Section: Discussionsupporting
confidence: 92%
“…More than half of the patients in our study were smokers; however, none of them died. The main symptom at the presentation in our study sample was melena (68.3%), followed by coffee-ground emesis (34.2%), which is similar to another Syrian study where out of 155 patients, 70% of them had melena [9]. However, in this study, the second most common symptom was hematemesis, while coffee-ground emesis happened in only 20% of the patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our patients were younger compared to contemporary studies and majority were in the third to sixth decade of life with a mean age of 40.9±15.9 years. This is in comparison to other studies by Villanueva et al[8], Travis et al[9], Liu et al[10], Daniela et al[11], Laursen et al[12], and Bitar et al[13] where in the mean age of studied subjects was 64.9±15; 64.9±15.3, 55.3±17.8,66,74, 52±16.8 years, respectively. Most of our patient population 361/480 (75%) was from rural areas but gender was equally distributed between the two groups.…”
supporting
confidence: 57%
“…Nonsteroidal anti‐inflammatory drugs (NSAIDS) and disease‐modifying anti‐rheumatic drugs (DMARDS) are the most commonly used drugs to treat rheumatoid arthritis (Thakur et al, 2018; Voshaar et al, 2022). However, these drugs can cause serious side effects such as peptic ulcers, intestinal bleeding and heart attacks (Bitar & Moussa, 2022; Chen et al, 2002; Nagata et al, 2016; Thomas et al, 2017). Doctors and scientists are eagerly awaiting new anti‐RA drugs that are highly effective and less toxic and can improve patient compliance.…”
Section: Introductionmentioning
confidence: 99%